Runs of homozygosity for autozygosity estimation and genomic analysis in production animals - Rebelato, Arnaldo Basso; Caetano, Alexandre Rodrigues (Pesquisa Agropecuaria Brasileira, 2018)
Runs of homozygosity (ROHs) are long stretches of homozygous genomic segments, identifiable by molecular markers, which can provide genomic information for accurate estimates to characterize populations, determine evolutionary history and demographic information, estimate levels of consanguinity, and identify selection signatures in production animals. This review paper aims to perform a survey of the works on the efficiency of ROHs for these purposes. Factors such as genetic drift, natural or artificial selection, founder effect, and effective population size directly influence the size and distribution of ROHs along the genome. Individually, genome estimates of consanguinity based on ROHs can be obtained using the FROH index, which is generally considered more accurate than indexes based on other types of genomic or genealogical information. High frequencies of specific ROHs in a population can be used to identify selection signatures. The results of recent studies with ROHs in domestic animals have shown the efficiency of their use to characterize herds in a reliable and accessible way, using genomic information.
Keywords: autozygosity; FROH; genotyping; selection signatures; single nucleotide polymorphism; SNPs